A Study of the Relationship between Magnesium Levels and the Lipid Profile - عوامة, محمد; حسون, شذى (Latakia University Journal -Medical Sciences Series, 2020)
The lipid profile is considered one of the most important predictive signs of cardiovascular disease, because high blood lipid levels are closely related to the formation of vascular plaques, which negatively affects cardiac perfusion.